REMEDIASI MISKONSEPSI HUKUM ARCHIMEDES DENGAN MODEL TWO STAY TWO STRAY BERBANTUAN LEMBAR KERJA BERSTRUKTUR - F03109027, FADRIANI; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The aim of this research was to knowed effectiveness about the application of cooperative learning model type two stay two stray assisted structured worksheets to remediation student misconceptions on Archimedes laws in SMP Negeri 2 Siantan Grade VIII Pontianak. The method was experimental with one group pretest-posttest design which is 32 students participated. The results showed that student misconception have reduction after remediation as much as 59.74%. Cooperative learning model type two stay two stray assisted structured worksheets effective to remediation student misconception with Effect Size as much as 1.8 (high category). Based on interview, 77.78% students are agree with that students actively participate in learning when remediation use cooperative learning model type two stay two stray assisted structured worksheets. This research is expected to be used as an alternative remediation activities for students to be able to overcome the misconceptions that experienced by students.Keywords: Remediation, Two Stay Two Stray.Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas remediasi penerapan model pembelajaran kooperatif tipe two stay two stray berbantuan lembar kerja berstruktur untuk meremediasi miskonsepsi siswa pada hukum Archimedes di kelas VIII SMP Negeri 2 Siantan Kabupaten Pontianak. Metode penelitian adalah eksperimen dengan rancangan One Group Pretest-Posttest Design dengan sampel penelitian berjumlah 32 siswa. Hasil menunjukkan bahwa persentase rata-rata penurunan miskonsepsi siswa setelah diberikan remediasi sebesar 59,74%. Model pembelajaran kooperatif tipe two stay two stray berbantuan lembar kerja berstruktur efektif untuk meremediasi miskonsepsi siswa dengan Effect Size sebesar 1,8 (berkategori tinggi). Berdasarkan wawancara, 77,78% siswa setuju sehingga siswa berpartisipasi secara aktif dalam pembelajaran ketika diremediasi menggunakan model pembelajaran kooperatif tipe two stay two stray berbantuan lembar kerja berstruktur. Penelitian ini diharapkan dapat digunakan sebagai alternatif kegiatan remediasi bagi siswa agar dapat mengatasi miskonsepsi yang dialami oleh siswa.Kata Kunci: Remediasi, Two Stay Two Stray.